Non-smoothness in the asymptotics of thin shells and propagation of singularities. Hyperbolic case - Karamian, Philippe; Sanchez-Hubert, Jacqueline; Sanchez Palencia, Évariste (Zielona Góra: Uniwersytet Zielonogórski)
We consider the limit behaviour of elastic shells when the relative thickness tends to zero. We address the case when the middle surface has principal curvatures of opposite signs and the boundary conditions ensure the geometrical rigidity.
Keywords: hyperbolic systems; propagation of singularities; shells